Ultraelastic and High‐Conductivity Multiphase Conductor with Universally Autonomous Self‐Healing. Issue 36 (9th November 2022) - Tolvanen, Jarkko; Nelo, Mikko; Alasmäki, Heidi; Siponkoski, Tuomo; Mäkelä, Piia; Vahera, Timo; Hannu, Jari; Juuti, Jari; Jantunen, Heli
Abstract: Next‐generation, truly soft, and stretchable electronic circuits with material level self‐healing functionality require high‐performance solution‐processable organic conductors capable of autonomously self‐healing without external intervention. A persistent challenge is to achieve required performance level as electrical, mechanical, and self‐healing properties optimized in tandem are difficult to attain. Here heterogenous multiphase conductor with cocontinuous morphology and macroscale phase separation for ultrafast universally autonomous self‐healing with full recovery of pristine tensile and electrical properties in less than 120 and 900 s, respectively, is reported. The multiphase conductor is insensitive to flaws under stretching and achieves a synergistic combination of conductivity up to ≈1.5 S cm −1, stress at break ≈4 MPa, toughness up to >81 MJ m −3, and elastic recovery exceeding 2000% strain. Such properties are difficult to achieve simultaneously with any other type of material so far. The solution‐processable multiphase conductor offers a paradigm shift for damage tolerant and environmentally resistant soft electronic components and circuits with material level self‐healing. Abstract : Ultraelastic and high‐conductivity organic conductor–elastomer blend with ultrafast and efficient self‐healing in universal conditions is demonstrated. The notch‐insensitive multiphase conductor, with a cocontinuous morphology and controllable heterogeneity, achieves synergistically optimized properties including toughness >80 MJ m −3, stress at break >4 MPa, elastic recovery >2000% strains, and conductivity up to ≈1.5 S cm −1 .